Secured Data Transmission Using Wavelet Based Steganography And Cryptography (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Steganography and cryptographic methods are used together with wavelets to increase the security of the data while transmitting through networks. Another technology, the digital watermarking is the process of embedding information into a digital (image) signal. Before embedding the plain text into the image, the plain text is encrypted by using Data Encryption Standard (DES) algorithm. The encrypted text is embedded into the LL subband of the wavelet decomposed image using Least Significant Bit (LSB) method. Then the inverse wavelet transform is applied and the resultant image is transmitted to the receiver. The receiver will perform the same operations in reverse order.